PENINGKATAN KEMAMPUAN LITERASI SISWA SEKOLAH DASAR MELALUI PENGGUNAAN BAHAN AJAR BERBASIS KEARIFAN LOKAL - Sri Hanipah; Wa Ode Siti Hamsinah Day (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The low literacy skills of students remain a major challenge in the field of education, including Merauke Regency, South Papua. One contributing factor is the use of learning materials that are insufficiently contextual and irrelevant to students’ lives. This study aims to determine the effectiveness of using local wisdom-based teaching materials in improving students literacy skills at Muhammadiyah Elementary School Merauke. The research employed a quantitative approach with a quasi-experimental design, using a one-group pretest-posttest model. The subjects of this study were 28 fourth-grade students selected through purposive sampling. Statistical analysis using the paired sample t-test showed a significant difference between the pretest and posttest scores (p < 0.05). The average literacy score increased from 61,18 in the pretest to 81,89 in the posttest, representing an improvement of 20,71%. These results indicate that the use of local wisdom-based teaching materials can enhance students’ literacy skills. The findings of this study are recommended for broader implementation by teachers in designing effective, meaningful, sustainable learning rooted in the nation’s culture to improve the quality of education, as well as to strengthen students’ identity and character from an early age. Keywords: Student Literacy 1, Teaching Materials 2, Local Wisdom 3, Elementary School 4